Nutritional vulnerability of early zoeal stages of the ornamental shrimp Lysmata ankeri (Decapoda: Caridea) - Barros-Alves, Samara de P.; de Almeida, Ariádine Cristine; Negreiros-Fransozo, Maria Lucia [UNESP]; Alves, Douglas Fernandes Rodrigues (My University, 2024)
The evaluation of the effects of early starvation and feeding on survival and growth in the early stages of the life cycle of ornamental marine caridean shrimp species is fundamental to establish adequate feeding protocols in their culture. In this study, we determine the nutritional vulnerability in the early larval stages of ornamental shrimp Lysmata ankeri exposed to different periods of starvation or feeding. The larvae were separated into three groups (zoea IZI, zoea II with ZI fed, and zoea II with ZI unfed) and subjected to two experiments: (1) point-of-no-return (PNR), comprising one or two days of initial starvation followed by feeding; and (2) point-of-reserve-saturation (PRS), comprising one or two days of initial feeding followed by starvation. Each experiment was still composed of two control groups: continuous feeding and continuous starvation. Larvae tolerated some periods of starvation, with a high PNR value (2.00) and low PRS (0.50). Longer periods of starvation influenced both growth and survival rates in zoea II stages. The nutritional vulnerability index for zoea I was 0.25, which represents a low dependence on food supply. In this study, it was observed that ornamental shrimp L. ankeri larvae hatch with energy reserves, presenting facultative primary lecithotrophy, in which they are able to moult from zoea I to zoea II using such reserves in the absence of food. In this sense, the early larvae stages (zoeas I and II) can tolerate a certain period of starvation, indicating the great potential of this species for aquaculture.
Keywords: aquaculture; larval development; Lysmatidae; starvation